Exploring early self-referential memory effects through ownership - Cunningham, S; Vergunst, F; Macrae, C; Turk, D (John Wiley and Sons, 2012)
The self-reference effect (SRE) is the reliable memory advantage for information encoded about self over material encoded about other people. The developmental pathway of the SRE has proved difficult to chart, because the standard SRE task is unsuitable for young children. The current inquiry was designed to address this issue using an ownership paradigm, as encoding objects in the context of self-ownership has been shown to elicit self-referential memory advantages in adults. Pairs of four- to six-year-old children (N=64) sorted toy pictures into self- and other-owned sets. A surprise recognition memory test revealed a significant advantage for toys owned by self, which decreased with age. Neither verbal ability nor Theory of Mind attainment predicted the size of the memory advantage for self-owned items. This finding suggests that contrary to some previous reports, memory in early childhood can be shaped by the same self-referential biases that pervade adult cognition. KEYWORDS: self, memory, development, ownership